1985
DOI: 10.1002/bit.260270407
|View full text |Cite
|
Sign up to set email alerts
|

Suggestions for the operation of radial flow cells in cell adhesion and biofouling studies

Abstract: An analysis of the radial flow cell is presented to show that the assumption of creeping laminar flow should be used cautiously. Simple models which account for the influence of fluid inertial forces over most of the width of the plate are reviewed. A modified Reynolds number is introduced which may be used to test the validity of the creeping flow solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…(3) was valid above a radius corresponding to a Re modified value of 0.27 for Eq. (4), which is in good agreement with Fryer et al (1985). Smaller radial positions correspond to higher values of Eq.…”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…(3) was valid above a radius corresponding to a Re modified value of 0.27 for Eq. (4), which is in good agreement with Fryer et al (1985). Smaller radial positions correspond to higher values of Eq.…”
Section: Introductionsupporting
confidence: 85%
“…Fryer et al (1985) expressed this condition mathematically. They introduced a modified Reynolds number and proposed a threshold value of 0.25 in order to compute the radial positions where Eq.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In particular, Fryer et al (1985) introduced the concept that observations of cell detachment at relatively small radial distances from the inlet can be difficult to interpret because the assumption of creeping flow becomes invalid: an inertial correction must be included in the analysis. Previous studies (e.g., Fowler and McKay, 1980;Cozens-Roberts et al, 1990) have suggested that the introduction of an empirical ''offset'' to the solution for creeping flow can correct for the presence of a finite-sized inlet.…”
Section: Introductionmentioning
confidence: 99%